Investigating the Impact of Lexico-Semantic Errors in EFL Iraqi University Students’ Performance in Essay Writing Skill - Hassan Jasim, Ban; Hassan Oraibi, Hawraa (International Journal of Psychosocial Rehabilitation, 2020)
The present study deals with "lexico-semantic errors." Such errors actually occur within second language learning. The problem of the study is that EFL Iraqi learners encounter some difficulties with semantic relations. It is aimed at revisiting the concepts of "lexico-semantic errors" and their types as well as measuring EFL Iraqi learners’ "lexico-semantic errors" through their writing. To achieve such aims, the The following procedures will be adopted: 1. Defining concepts of writing, non-native speaker, and "lexico-semantic errors." 2. Presenting the basic types of "lexico-semantic errors." 3. Following James’s (1998)’ model. 3. The main points are outlined. It is hypothesized that there is a wrong choice of collocation belonging to the translation from Arabic to English. Additionally, "lexico-semantic errors" are caused by transferring some ideas from first language acquisition. As for the steps being adopted, As far as the data analysis, it is limited to (20) students of the EFL Iraqi learners who are fourth-year students Department of English/College of Education for Humanities University of Thi Qar for the academic year 2020-2021. The finding is that students fail to use accurate lexemes when writing their essays.